Adaptive Backstepping Method for Stabilizing Systems of Fractional Order Ordinary Differential Equations - Jassim, Asad; S. Fadhel, Fadhel; N. Hasan, Nabaa (Al-Nahrain Journal of Science, 2021)
In this paper the method of adaptive backstepping for stabilizing and solving system of ordinary and partial differential equations will be used and applied to investigate and study the stability linear systems of Caputo fractional order ordinary differential equations. The basic idea of this approach is to find a quadratic Lyapunov functions for stabilizing the subsystems.